2006
DOI: 10.1038/ng1946
|View full text |Cite
|
Sign up to set email alerts
|

Convergent adaptation of human lactase persistence in Africa and Europe

Abstract: A SNP in the gene encoding lactase (LCT) (C/T-13910) is associated with the ability to digest milk as adults (lactase persistence) in Europeans, but the genetic basis of lactase persistence in Africans was previously unknown. We conducted a genotype-phenotype association study in 470Correspondence should be addressed to S.A.T. (Tishkoff@umd.edu).. 9 These authors contributed equally to this work. AUTHOR CONTRIBUTIONS S.A.T. conceived and supervised the study. S.A.T., K.P., H.M.M., A.R., J.B.H., M.O., M.I., S.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
1,100
4
28

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,323 publications
(1,207 citation statements)
references
References 45 publications
53
1,100
4
28
Order By: Relevance
“…5 In other populations, different polymorphisms in the LCT promoter have been also shown to be associated with lactase persistence. 6 Several studies support the perspective that these differences in lactase persistence between populations can be ascribed to processes of positive selection. 1,2 Indeed, it has been suggested that the frequency of lactase persistence has increased in several populations as cattle domestication and dairy consumption was introduced in Europe.…”
Section: Introductionmentioning
confidence: 93%
“…5 In other populations, different polymorphisms in the LCT promoter have been also shown to be associated with lactase persistence. 6 Several studies support the perspective that these differences in lactase persistence between populations can be ascribed to processes of positive selection. 1,2 Indeed, it has been suggested that the frequency of lactase persistence has increased in several populations as cattle domestication and dairy consumption was introduced in Europe.…”
Section: Introductionmentioning
confidence: 93%
“…This region has been implicated as the genetic basis for lactase persistence in several African populations, including some from Kenya, and has evidence of having undergone recent, strong positive selection. 30 The first region on chromosome 6 (29.77-30.17 Mb) is coincident with the HLA class I region, a portion of the genome well known as being under strong selective pressure due to its importance in immune system function. 31 The second highest peak on chromosome 6 (130.61-130.81 Mb) contains only two known genes, KIAA1913 and SAMD3.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we have only tested one of several LP alleles. Other LP alleles have arisen independently in other groups (Imtiaz et al 2007;Ingram et al 2007Ingram et al , 2009Tishkoff et al 2007;BĂŒning et al 2004;Itan et al 2010). It is possible that not all individuals who lack the particular LP allele tested are in fact lactose intolerant.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that the selective pressures that led to the LP allele being common in these geographic regions originated from the dairying practices begun by early European and West Asian farmers \10,000 years ago (Bersaglieri et al 2004;Scrimshaw and Murray 1988). This and other lactase persistence alleles found in African and other populations (Imtiaz et al 2007;Ingram et al 2007;Tishkoff et al 2007) likely conferred a selective advantage by providing an additional source of energy and preventing the malabsorption of dairy nutrients associated with lactose (Debongnie et al 1979).…”
Section: Introductionmentioning
confidence: 99%